The Association between Anthropometry Indices and Serum Concentrations of Gamma-Glutamyl Transferase, Alkaline Phosphatase, Alanine Aminotransferase, and Aspartate Aminotransferase. (22nd November 2021) - Sobhani, Sahar; Aryan, Reihaneh; AkbariRad, Mina; Ebrahimi Miandehi, Elahe; Alinezhad-Namaghi, Maryam; Sobhani, Seyyed Reza; Raji, Sara
Abstract : Background . Nowadays, metabolic syndrome (MetS) has become a great public health crisis that threatens too many lives worldwide. Many previous studies have been investigated the association between MetS and anthropometric indices. This study is aimed at investigating the association between anthropometric indices with gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), alanine aminotransferase (ALT), and aspartate aminotransferase (AST). We were using data from a large population-based cohort of seemingly healthy women and men. Methods . A total of 7216 participants were included in this study. The serum levels of GGT, ALP, ALT, and AST with bioimpedance measures were obtained at the time of enrollment. Multiple regression analysis was performed to assess the relationship between anthropometric indices and serum levels of the aforementioned laboratory tests. Results . Serum levels of GGT, ALP, ALT, and AST significantly correlated with body mass index (BMI). Only ALP had a significant association with visceral fat area (VFA). AST, ALT, and ALP levels had a positive correlation with 50 kHz whole-body phase. Conclusion . From the findings of this study, body mass index consistently appeared a good predictor of elevated hepatic enzymes and triglycerides. Thus, it can be helpful in clinical settings to identify patients at risk of nonalcoholic fatty liver disease, which is closely related to metabolic syndrome.